Norway : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This paper presents the staff report for Norway's 2009 Article IV Consultation on economic developments and policies. Unemployment remains low, and key short-term indicators point to a continued recovery. Norway's resilience has been underpinned by substantial macroeconomic stimulus, buoyant activity in the offshore hydrocarbon sector, high public sector employment, limited dependence on the hardest-hit segments of global manufacturing, and the relative stability of the domestic financial sector. Brisk oil sector activity, rising asset prices, and rapid credit growth have boosted the domestic demand.